2012
DOI: 10.4314/ahs.v12i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic activity of <i>Commelina africana</i> and <i>Ageratum conyzoides</i> in relation to their mineral composition

Abstract: Background: Many plants with antidiabetic properties probably act in part through their content of fibre, vitamins, bioactive or mineral content Objectives: This study investigated the mineral, proximate, phytochemical compositions and hypoglycaemic effect of Commelina africana and Ageratum conyzoides extracts in diabetic rats, and the likely relationship between this property and the mineral, proximate and phytochemical compositions of the plants . Methods:The plants were subjected to mineral, proximate compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 18 publications
(22 reference statements)
1
36
0
Order By: Relevance
“…Liver can be damaged during hyperglycemic conditions due to the increase of blood glucose levels exceeding normal (Sari et al, 2010). It is characterized by the presence of blood glucose more than 126 mg/dL (Prasetyo et al, 2016), which can cause glucose availability in cells decreases so that it can trigger the occurrence of gluconeogenesis in liver cells (Agunbiade et al, 2012). These conditions over a long period of time can lead to increase Reactive Oxygen Species (ROS) compounds that can bind to hepatocyte structures, thereby able to cause hepatocyte damage which is begin with degeneration, up to cellular necrosis (Maulida et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Liver can be damaged during hyperglycemic conditions due to the increase of blood glucose levels exceeding normal (Sari et al, 2010). It is characterized by the presence of blood glucose more than 126 mg/dL (Prasetyo et al, 2016), which can cause glucose availability in cells decreases so that it can trigger the occurrence of gluconeogenesis in liver cells (Agunbiade et al, 2012). These conditions over a long period of time can lead to increase Reactive Oxygen Species (ROS) compounds that can bind to hepatocyte structures, thereby able to cause hepatocyte damage which is begin with degeneration, up to cellular necrosis (Maulida et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This could as well account for the many therapeutic uses of the plant. For example, sodium and potassium are responsible for maintaining the electrolyte balance of the cells, water balance and distribution, blood pressure, acid-base balance, muscle and cell nerve function, heart function, kidney and adrenal functions (Agunbiade et al, 2012). These elements (sodium and potassium) were present in significant amounts in the leaves of H. hemerocallidea.…”
Section: Resultsmentioning
confidence: 99%
“…3.12 | Anti-diabetic activity Nyunai, Manguelle-Dicoum, Njifutie, Abdennebe, and Gerard (2010) reported anti-diabetic activity from the aqueous extract of A. conyzoides leaves in normoglycaemic and streptozotocin-induced diabetic rats (Nyunai et al, 2010). Agunbiade, Ojezele, Ojezele, and Ajayi (2012) have reported that the aqueous leaf extract of A. conyzoides has showed the hypoglycemic activity in the tested animals. Distilled water and ethylacetate leaf extracts of A. conyzoides have been found to be antidiabetic effect in Streptozotocin-induced diabetic rats (Agbafor et al, 2015).…”
Section: Anthelmintic Activitymentioning
confidence: 97%
“…conyzoides leaves in normoglycaemic and streptozotocin‐ induced diabetic rats (Nyunai et al, ). Agunbiade, Ojezele, Ojezele, and Ajayi () have reported that the aqueous leaf extract of A . conyzoides has showed the hypoglycemic activity in the tested animals.…”
Section: Pharmacologymentioning
confidence: 99%